Formulation Development and In Vitro Evaluation of Metformin Hydrochloride Matrix Tablets Based on Hydroxypropyl Methyl Cellulose (Stamford Journal of Pharmaceutical Sciences, 2009)
An attempt was to formulate the oral sustained release Metformin hydrochloride matrix tablets by using hydroxyl methyl cellulose polymer (HPMC) as rate controlling factor and to evaluate drug release parameters as per various release kinetic models. The tablets were prepared by direct compression method. The granules were evaluated for angle of repose, loose bulk density, tapped bulk density, compressibility index, total porosity, drug content etc. and showed satisfactory results. The tablets were subjected to thickness, weight variation test, drug content, hardness, friability and in vitro release studies. The in vitro dissolution study was carried out for 8 hours using United States Pharmacopoeia USP 2 (paddle-type dissolution apparatus) in phosphate buffer (pH 7.4) as dissolution media. All the tablet formulations showed acceptable pharmacotechnical properties and complied with pharmacopoeial specifications. The release mechanisms were explored and explained with zero order, first order, Higuchi, Korsmeyer and Hixson-Crowell equations. The results indicated that a decrease in release kinetics of the drug was observed by increasing the polymer concentration. Kinetic modeling of in vitro dissolution profiles revealed the drug release mechanism ranges from diffusion controlled or Fickian transport to anomalous type or non-Fickian transport, which was only dependent on the type and amount of polymer used. The drug release followed both diffusion and erosion mechanism in all cases. Besides, this study explored both of the optimum concentration and the effect of polymer on drug release pattern from the tablet matrix for 8 hours period. Key Words: Metformin HCl, Sustained release, Hydrophilic matrix, HPMC, Direct compression Â  doi:10.3329/sjps.v1i1.1808 S. J. Pharm. Sci. 1(1&2): 51-56